Continuation of Hemodialysis in a Patient With Global Hypoxic Brain Injury: Ethical Considerations and Factors That May Influence Decision Making. Issue 2 (23rd April 2022) - Vickey, Terri; Frechman, Erica
Abstract : Survivors of an out-of-hospital cardiac arrest are at a high risk of mortality and morbidity especially when there is resultant global hypoxic brain injury. In these situations, the patient's degree of neurologic recovery may be uncertain and family decision making is often difficult. Decision making may also be complicated by the age of the patient and one's underlying cultural and spiritual beliefs stressing the importance of patient- and family-centered care. In this article, this clinical case demonstrates the challenges in decision making and highlights the importance of communication among the health care team and the family to align the patient's goals, values, and preferences in light of a poor neurological prognosis.